Learning jQuery. - Chaffer, Jonathan (Community experience distilled., 2013)
Step through each of the core concepts of the jQuery library, building an overall picture of its capabilities. Once you have thoroughly covered the basics, the book returns to each concept to cover more advanced examples and techniques. This book is for web designers who want to create interactive elements for their designs, and for developers who want to create the best user interface for their web applications. Basic JavaScript programming and knowledge of HTML and CSS is required. No knowledge of jQuery is assumed, nor is experience with any other JavaScript libraries.